Australian Christians in conflict and unity ; v. 1 - Engel, Frank 1911- (Melbourne, VIC JBCE, 1984)
Contents : v. 1 : Conflict and Unity, 1788-1926. Includes bibliographical references and index.
Keywords: Church history -- modern period -- Australia; Christian union -- history -- Australia